1988
DOI: 10.1111/j.1467-8624.1988.tb03261.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression and Motherese: Temporal and Intonational Features

Abstract: Children of depressed parents are at increased risk for depression and other developmental problems. Recent research indicates that disturbances exist in face-to-face interactions between depressed mothers and their infants. In the present study, the effects of maternal depression on motherese, an interactive behavior that plays a significant role in affective, cognitive, and social development, were examined. 2 paralinguistic features of motherese were examined: temporal parameters of utterances and pauses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 7 publications
4
99
0
5
Order By: Relevance
“…Research has found that voice quality, pitch and intonation are affected by maternal mood symptoms (Bettes, 1988;Scherer, 1986). Given that within community samples, mothers show significant variation in maternal psychological health (also see Jones et al, 2013), differences in voice quality may also occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that voice quality, pitch and intonation are affected by maternal mood symptoms (Bettes, 1988;Scherer, 1986). Given that within community samples, mothers show significant variation in maternal psychological health (also see Jones et al, 2013), differences in voice quality may also occur.…”
Section: Discussionmentioning
confidence: 99%
“…The stranger's voice was recorded under the same conditions. The same stranger's voice recording was presented to all infants in order to control for differences in the length of the recording and in voice quality, pitch and intonation (see Bettes, 1988;Scherer, 1986).…”
Section: Face/voice Stimulimentioning
confidence: 99%
“…Depressed mothers do not modify their speaking style (43,44) to produce the exaggerated "motherese" that infants prefer (45)(46)(47)(48), and which can highlight speech sound differences (49). Newborns of depressed mothers fail to show face/voice preference (22) whereas older infants do not learn as well from their mothers' infant-directed speech (50).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research points to disordered mother-infant interactions as a significant correlate of maternal depression (Cohn & Campbell, 1992), and one that may affect infant cognitive development through consequences of dysregulated arousal and attention (Field, 1994;Tronick & Gianino, 1996). Prolonged interactions with a partner who is low in sensitivity and contingent responding, as are depressed caregivers (Bettes, 1988;Murray et al, 1993;Zlochower & Cohn, 1991) may, through a conditioning process such as latent inhibition (Lubow, 1989) or learned irrelevance (Linden et al, 1997), teach an 5 Prior research in our laboratory has investigated whether matches versus mismatches in affective information in voices and faces affect infant learning. For example, Kaplan et al (1997) showed that ID speech rated as happy-sounding by adults was equally well associated with a smiling or a sad face by four-month-old infants of non-depressed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Because ID speech produced by mothers with comparatively more symptoms of depression was known to possess a significantly lower extent of fundamental frequency (F 0 ) modulation (Bettes, 1988) -an important acoustic cue in maternal ID speech (Fernald & Kuhl, 1987) -we predicted that ID speech recorded from mothers with comparatively more symptoms of depression would be less effective at promoting voice-face associations in this paradigm. Kaplan, Bachorowski, & Zarlengo-Strouse (1999) recorded brief segments of ID speech from 20 mothers who varied in symptoms of depression, and later used them to signal a smiling face reinforcer for 20 groups of 4-month-old infants of non-depressed mothers.…”
mentioning
confidence: 99%